R.P. Botha, G. Kroes en C.H. Winckler. Afrikaanse Idiome en ander Vaste Uitdrukkings - Lubbe, H.J. (Lexikos, 1995)
Review of R.P. Botha, G. Kroes en C.H. Winckler. Afrikaanse Idiome en ander Vaste Uitdrukkings